ANALISA KETERSEDIAN ALOKASI KANAL RADIO KOMUNITAS DI KOTA DENPASAR - Nurya Savitri, Estry; Wiharta, Dewa Made; Sukadarmika, Gede (Jurnal SPEKTRUM; Vol 7 No 3 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i03.p7, 2020)
In this study aims to analyze the use of Community radio frequency (Rakom) in Denpasar and by analyzing the number of channels allocated frequency and the amount of authorized community radio authorization in the city of Denpasar. It is hoped that the study is expected to give an overview of how availability community radio channels in Denpasar City area. To be able to avoid interference in the service area on radio community broadcasts in the city of Denpasar. Conducted analysis and simulation of mapping of new LPK Radio services (community broadcasting institutions). The measured parameters include the calculation of the Budget link and the measurement results obtained in the field which is then compared with the theory. Based on the results of simulated analysis mapping and calculations used, in the area of Denpasar city there can only be 2 (two) radio communities.